2011
DOI: 10.1007/s10450-011-9349-z
|View full text |Cite
|
Sign up to set email alerts
|

Selective adsorption of 2,3-DCDD and 1,2,3,4-TCDD on *BEA, EMT, FAU and MFI-type zeolites as alternative adsorbents for on-line dioxin monitoring

Abstract: The aim of this study is to evaluate the capabilities of zeolites as selective sorbents for on-line dioxin monitoring. The adsorption isotherms of 2,3-DCDD and 1,2,3,4-TCDD from isooctane on several zeolites with different pore sizes (*BEA, EMT, FAU and MFI-type zeolites) are determined. Selective adsorption is shown for FAU and EMTtype zeolites. 2,3-DCDD is adsorbed by FAU with the highest adsorption capacity and affinity while 1,2,3,4-TCDD is not adsorbed whatever the zeolites. The adsorption of 2,3-DCDD ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…In order to reduce or eradicate pollution, different techniques are possible such as condensation, 1 catalytic oxidation, 2,3 membrane separation 3 and adsorption. [4][5][6][7][8] The latter is generally preferred due to its good cost-effectiveness and ease of use. Adsorbent materials such as zeolites have been successfully used to solve the contamination problem, especially in the space and environmental industries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to reduce or eradicate pollution, different techniques are possible such as condensation, 1 catalytic oxidation, 2,3 membrane separation 3 and adsorption. [4][5][6][7][8] The latter is generally preferred due to its good cost-effectiveness and ease of use. Adsorbent materials such as zeolites have been successfully used to solve the contamination problem, especially in the space and environmental industries.…”
Section: Introductionmentioning
confidence: 99%
“…Adsorbent materials such as zeolites have been successfully used to solve the contamination problem, especially in the space and environmental industries. [4][5][6][9][10][11][12][13][14][15][16] Zeolites are aluminosilicate materials made from AlO 4 and SiO 4 tetrahedra sharing their oxygen vertices. Thanks to their high thermal stability coupled with an intrinsic Brönsted acidity, their interesting sorption and catalytic properties are now wellknown.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, FAU-type zeolites possess a large microporous volume, accessible even to pollutants with a significant molecular size. 7 Moreover, its chemical composition can be fine-tuned through (1) a broad interval of Si/Al ratios, with which it can be synthesized or postsynthetically modified (1 < Si/Al < ∞), 8 and (2) cationic exchange involving a large number of extra-framework cations. 9 The FAU framework is built on the basis of fused double six-rings (D6Rs), (also called hexagonal prisms) and sodalite cages (also called β-cages).…”
Section: Introductionmentioning
confidence: 99%
“…Zeolites, aluminosilicate crystalline materials with an ordered microporous structure, formed by linking silicon and aluminum tetrahedra, aroused a huge scientific interest related to a wide number of their potential applications, in particular, in environmental remediation. Among the approximately 250 identified zeolite structures, the faujasite ( FAU ) has attracted a special attention due to its interesting structural, textural, and chemical properties. Indeed, FAU-type zeolites possess a large microporous volume, accessible even to pollutants with a significant molecular size . Moreover, its chemical composition can be fine-tuned through (1) a broad interval of Si/Al ratios, with which it can be synthesized or postsynthetically modified (1 < Si/Al < ∞), and (2) cationic exchange involving a large number of extra-framework cations …”
Section: Introductionmentioning
confidence: 99%
“…Authors of this study have proposed to determine the adsorption properties of zeolites with solutions of dioxins in isooctane. Adsorption isotherms showed that 2,3-DCDD has been adsorbed in the micropores of FAU-NaX zeolite with very high affinity, regarding the adsorbent micropore size and dynamic molecule size, while the adsorption of 1,2,3,4-TeCDD has been limited to the external --surface [25]. Furthermore, the authors explained that the nature of the charge compensating cations could have an influence on the congener adsorption in the micropores [26].…”
mentioning
confidence: 99%